Differential effects of PCSK9 variants on risk of coronary disease and ischaemic stroke - Hopewell, J; Malik, R; Valdes-Marquez, E; Worrall, B; Collins, R; METASTROKE Collaboration of the ISGC (Oxford University Press, 2017)
Aims: PCSK9 genetic variants that have large effects on low density lipoprotein cholesterol (LDL-C) and coronary heart disease (CHD) have prompted the development of therapeutic PCSK9-inhibition. However, there is limited evidence that PCSK9 variants are associated with ischaemic stroke (IS). Methods and Results: Associations of the loss-of-function PCSK9 genetic variant (rs11591147; R46L), and 5 additional PCSK9 variants, with IS and IS subtypes (cardioembolic, large vessel and small vessel) were estimated in a meta-analysis involving 10,307 IS cases and 19,326 controls of European ancestry. They were then compared with the associations of these variants with LDL-C levels (in up to 172,970 individuals) and CHD (in up to 60,801 CHD cases and 123,504 controls). The rs11591147 T allele was associated with 0.5 mmol/L lower LDL-C level (P=9x10-143) and 23% lower CHD risk (odds ratio [OR]: 0.77, 95% CI: 0.69–0.87, P=7x10-6 ). However, it was not associated with risk of IS (OR: 1.04, 95% CI: 0.84–1.28, P=0.74) or IS subtypes. Information from additional PCSK9 variants also indicated consistently weaker effects on IS than on CHD. Conclusions: PCSK9 genetic variants that confer life-long lower PCSK9 and LDL-C levels appear to have significantly weaker, if any, associations with risk of IS than with risk of CHD. By contrast, similar proportional reductions in risks of IS and CHD have been observed in randomized trials of therapeutic PCSK9-inhibition. These findings have implications for our understanding of when Mendelian randomization can be relied upon to predict the effects of therapeutic interventions.